Errors in EFL Students' Reflective Journal Writing on Online Blogging: A Review - Kurniati, Eka Yuni; Rahman, Benni Ichsanda (Universitas Negeri Medan, 2021)
Reflective journals could encourage students to develop the habit of writing regularly and hone students' critical thinking skills since they will start investigating their explanation and put all of the ideas into writing in their own words.This study was aimed to determine the types of errors written by an EFL student in her reflective journal writing on her blog account,the manner in which the EFL student generated errors, and the sensible reasons that affected the EFL student in producing her reflective journal writing errors. This study was classified as a qualitative content analysis. The data for this research came from ten reflective journal entries by an EFL student on her blogging account. Purposive sampling was used to collect the data. Furthermore, the researcher discovered five distinct sorts of errors in an EFL student's reflective journal writing on her online blogging platform. They included errors in time, omission errors, insertion errors, parts of speech errors, and other errors. Basically, the average number of errors actually happened unintentionally; the EFL student committed errors by omitting, adding, and disordering certain words while constructing sentences. Numerous variables contributed to the incidence of errors, including interlingua and intralingua transfer, a lack of vocabulary, and the use of ineffective translation methods.